PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Siti Hawa Holifah, (2021)
This study was conducted to examine the effect of institutional ownership, managerial ownership, and profitability on firm value in industrial sector companies listed on the IDX-IC in 2017-2019 by purposive sampling method. This study uses a sample of 60 industrial companies. The technique for analyzing the data in this study used a regression model selection test, classical assumption test, panel data linear regression, and partial hypothesis testing (t test) with EViews 10. Based on the results of data analysis, it can be concluded that (1) Institutional ownership has no effect on firm value, (2) Managerial ownership has no effect on firm value, (3) Profitability has no effect on firm value, and the control variable, namely (4) Firm size has no effect on firm value.